Hegel on beauty - Peters, Julia (Routledge studies in nineteenth-century philosophy, 2015)
1. The anthropological roots of beauty -- 2. Hegel on beauty, nature and art : towards a novel interpretation -- 3. The value of beauty, aesthetic experience, and the aesthetic human ideal -- 4. The beautiful character and its limits -- 5. Beyond beauty : the pain of inner division -- 6. Modern beauty.